2017
DOI: 10.1108/ssrp-04-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Why do young adults vote at low rates? Implications for education

Abstract: Purpose -The purpose of this paper is to focus on the political attitudes, experiences, and habits of young adults in the USA, with particular focus on their voting habits. Since young adults are just beyond Kindergarten-12 (K-12) schooling they are the voting segment arguably most affected by this experience, and their political habits and attitudes inform educational policy and practice. The concern under focus is that studies have found that this group votes at low rates, especially during mid-term election… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…The large majority of young adults who were surveyed and interviewed for this study reported that they believed that voting matters, whether they voted or did not vote in 2018. And those who voted in 2018 seemed more interested, knowledgeable, and confident in speaking or posting information on social media about politics, corroborating previous research (Knoester & Kretz, 2017; The Knight Foundation, 2015).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The large majority of young adults who were surveyed and interviewed for this study reported that they believed that voting matters, whether they voted or did not vote in 2018. And those who voted in 2018 seemed more interested, knowledgeable, and confident in speaking or posting information on social media about politics, corroborating previous research (Knoester & Kretz, 2017; The Knight Foundation, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…We argue that low access to necessary information about voting, especially regarding local elections, also contributes to low voter turnout. Low information, and lack of broad commitment to public education about these issues, along with pressure on schools to avoid controversial issues, including the banning of books in some locations, can also be understood to be a form of voter suppression (Knoester & Kretz, 2017; Doyle, 2014; Foerstel, 2002; Hasen, 2012; Johnson & Weaver, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Se sabe que, a partir de noviembre del 2017, la cifra máxima de escritura en esta red social pasó de 140 a 280 caracteres, lo cual ha permitido incrementar los contenidos de los mensajes y el establecimiento del tipo de participación que los usuarios proyectan. De esta forma, la transmisión y el análisis de los fenómenos sociales a través de las redes sociales cobran importancia para conocer la manera en que se exponen e intercambian impresiones con el resto de los cibernautas, cómo interpretan la información y sus reacciones ante hechos que afectan a su comunidad o a alguna otra en el mundo (Knoester y Kretz, 2017).…”
Section: Introductionunclassified